Sistem Pendukung Keputusan Penerapan Metode EDAS Dalam Menyeleksi Konten Youtube Terbaik Untuk Anak Usia Dini - Salmon Salmon; Pitrasacha Adytia; Muhammad Fahmi (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2023)
Youtube is an online video platform that has become one of the most popular and widely used websites in the world. YouTube's main goal is to provide facilities for content creators to upload the videos they create, interact with their audiences and provide users with a better and innovative video viewing experience, with features such as video browsing tailored to the user's interests and improved video quality. YouTube content is a term that refers to videos or other material uploaded to the YouTube platform, which is currently one of the largest websites in the world for sharing videos. In selecting Youtube content for early childhood, there are several criteria, namely: entertaining, not pornographic elements, increasing insight, not being violent, being creative. The results showed that the EDAS (Evaluation Based on Distance From Average Solution) method can provide an objective and accurate assessment by considering various relevant criteria. So as to produce YouTube content Omar and Hana ranked first (A2) with a score obtained 0.084 is YouTube content that is appropriate for children at an early age.